2008
DOI: 10.1016/j.ijid.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The globalization of leptospirosis: worldwide incidence trends

Abstract: Leptospirosis is a re-emerging zoonosis of global importance and unique environmental and social correlations. Attempts at global co-ordination and recognition of the true burden of an infectious disease with significant mortality should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
335
0
33

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(394 citation statements)
references
References 34 publications
6
335
0
33
Order By: Relevance
“…Moreover, leptospirosis is associated with floodwaters following monsoons [11][12][13]. It has also been suggested that temperature and rainfall considerably increase the incidence of DF infections [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, leptospirosis is associated with floodwaters following monsoons [11][12][13]. It has also been suggested that temperature and rainfall considerably increase the incidence of DF infections [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…1 The annual incidence is estimated at 10-100 cases per 100,000 population in tropical countries. 2 The early phase of leptospirosis manifestations lasts 3-7 days and includes fever, headaches, myalgia (especially in the calves), nausea, vomiting, malaise, and conjunctival hyperemia. Only 10% progress to the second phase: the Weil syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…A doença se estendeu além das áreas rurais e tornou-se uma das causas de epidemias em comunidades urbanas dos países em desenvolvimento (Pappas et al 2008). Nesses países, como…”
Section: Introductionunclassified
“…A doença se estendeu além das áreas rurais e tornou-se uma das causas de epidemias em comunidades urbanas dos países em desenvolvimento (Pappas et al 2008). Nesses países, como no caso do Brasil, a sua ocorrência está relacionada ao acelerado e desordenado processo de expansão urbana, onde grande parte da população passou a habitar áreas da periferia, sem o mínimo de condições de infraestrutura e saneamento, facilitando a manutenção de agentes patogênicos nocivos à saúde animal e humana.…”
Section: Introductionunclassified